ORIENTASI POLITIK MASYARAKAT DALAM PEMILUKADA KABUPATEN LAMPUNG BARAT 2012 - Noralia Priyanti; Robi Cahyadi Kurniawan (Program Studi Administrasi Negara Universitas Serang Raya, 2014)
Conditions of society's political orientation Pekon Sebarus in 2012 West LampungRegional Election based on the competition between the incumbent candidate and the new candidate. The researcher had observated the situation in Pekon Sebarus, society always actively participating in every general election. The new candidate from Pekon Sebarus, Pieterson, had been considered would make new political orientation in Pekon Sebarus Society. The main problem of this research is How conditions of society's political orientation Pekon Sebarus in 2012 West Lampung Regional Election. Which is the most dominant political orientation used by the Pekon Sebarus society. This research aimed to know conditions of society's political orientation Pekon Sebarus in 2012 West Lampung RegionalElection. The method which is used is quantitative method and supported by qualitative analysis. Data collecting technique used primer data and secondary data. Data analysis technique used by single table which is, putting the data from the questioner into the tableframe for calculating the frequency and making percentage as an elaboration of the final result. The result showed that conditions of society's political orientation Pekon Sebarus in 2012 West Lampung Regional Election there are two approaches which contained in high category. These are Structural approach and rasional-choosing approach. Structuralapproach choosed by 42% respondent whereas rasional-choosing approach choosed by 31% respondent in 2012 West Lampung Regional Election.